2010
DOI: 10.1088/0960-1317/20/5/055007
|View full text |Cite
|
Sign up to set email alerts
|

A novel passive micromixer based on unbalanced splits and collisions of fluid streams

Abstract: A new passive micromixer based on the concept of unbalanced splits and cross-collisions of fluid streams is designed and fabricated. Experimental and numerical studies have been carried out on the micromixer at Reynolds numbers ranging from 10 to 80. The three-dimensional Navier-Stokes equations have been used to analyze the mixing and flow behavior of the micromixer, which is composed of two sub-channels of unequal widths which repeatedly undergo splitting and recombination. The difference between the mass fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 156 publications
(97 citation statements)
references
References 29 publications
1
90
0
Order By: Relevance
“…However, the use of flow constrictions requires higher pumping power due to the high pressure drop. Unbalanced splits and cross-collisions of fluid streams were investigated numerically and experimentally by Ansari et al [27]. Their results demonstrate that mixing performance is maximized when the width of the major sub-channel is twice that of the minor sub-channel, and the lowest mixing performance is obtained for equal sub-channel widths.…”
Section: Open Accessmentioning
confidence: 99%
“…However, the use of flow constrictions requires higher pumping power due to the high pressure drop. Unbalanced splits and cross-collisions of fluid streams were investigated numerically and experimentally by Ansari et al [27]. Their results demonstrate that mixing performance is maximized when the width of the major sub-channel is twice that of the minor sub-channel, and the lowest mixing performance is obtained for equal sub-channel widths.…”
Section: Open Accessmentioning
confidence: 99%
“…In the last decade, for better mixing efficiency, many researchers have made great effort to develop various types of passive micromixers composed of 2-D curved channel with radial baffles, 23 2-D cylindrical grooves adjoining to the main straight channel 24 and 2-D structures based on the concept of the splitting and recombination. [25][26][27][28] These micromixers did exhibit high performance at high flow rates, but at a low level the channel geometries cannot result in obvious vortices or chaotic advection and the contact surface between the streams are usually vertical without rotation and expansion, so these micromixers are not effective at lower Reynolds number unless these micromixers have a longer mixing length.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the mixing was improved due to the multidirectional vortices include Dean and separation vortices. Mixing of water and ethanol in a new passive micromixer based on the concept of unbalanced splits and cross-collisions of fluid streams were studied numerically and experimentally by Ansari et al (2010). The main channel was split into two sub-channels that subsequently recombine after a certain distance and the width of two sub-channels could be unequal.…”
Section: Nomenclaturementioning
confidence: 99%